A systematic review evaluating the use of ultrasound in the identification of osteochondrosis in horses. (April 2022) - Hoey, S.; Stokes, D.; McAllister, H.; Puggioni, A.; Skelly, C.
Abstract: Osteochondrosis is commonly encountered in young horses, with welfare, performance, and economic effects. Consequently, pre-purchase radiographic screening for osteochondrosis is routinely performed. Ultrasonographic examination of articular cartilage and osteochondrosis lesions are described in the literature with many case series or single case reports published. This systematic review was undertaken to examine the evidence for using ultrasonography in comparison to traditional radiography, arthroscopy or necropsy findings in the detection of osteochondrosis. The systematic review identified a paucity of studies in which there was marked variation in the populations, sample size, methods and results reported. Currently, there is no strong evidence confirming the diagnostic accuracy and validity of ultrasonography in the detection of osteochondral lesions in the relevant joints in horses. Highlights: Ultrasonography (US) is commonly used to diagnose osteochondrosis (OC) in horses. Few peer reviewed studies have confirmed the diagnostic validity of US to detect OC. Studies had variable breeds, ages and joints investigated. Sensitivity and specificity for ultrasonography ranged between 33% and 100%.